2000
DOI: 10.2527/2000.78112942x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of induced corpora lutea to maintain pregnancy in beef cows.

Abstract: Experiments were conducted in beef cows without a primary CL, in which pregnancy had been maintained with exogenous progestogen. In preliminary trials, replacement CL induced ipsilateral to the embryo and after, rather than before, d 36 of pregnancy, maintained more pregnancies after withdrawal of exogenous progestogen (13/13 vs 2/6; P < 0.05). In Exp. 1, in cows with replacement CL induced by treatment with hCG on d 28 of pregnancy, treatment with flunixin meglumine on d 31 through 37 did not increase mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 30 publications
0
20
1
1
Order By: Relevance
“…pregnancy following luteectomy or PGF 2a -induced luteal regression [31,32], it is unlikely that the CL secretes anything other than progesterone, which is essential for pregnancy maintenance. Interestingly, the CL on Day 13 of pregnancy in sheep is exposed to higher basal levels of PGF 2a compared with the CL on Day 13 of the cycle [33].…”
mentioning
confidence: 99%
“…pregnancy following luteectomy or PGF 2a -induced luteal regression [31,32], it is unlikely that the CL secretes anything other than progesterone, which is essential for pregnancy maintenance. Interestingly, the CL on Day 13 of pregnancy in sheep is exposed to higher basal levels of PGF 2a compared with the CL on Day 13 of the cycle [33].…”
mentioning
confidence: 99%
“…This problem has been well documented in cattle (beef and dairy) calving without a CL [10,11,13,14], and although it has been reported that induced luteal tissue was capable of supporting pregnancy in luteoctomized cattle in the absence of maintenance progestin [12,17,18] the success rate was low when the induced luteal tissue was located on the contralateral ovary to the gravid uterine horn [12]. Only one study reports induced luteal tissue doi: 10.7243/2054-3425-2-1 continuing a bovine pregnancy to term [19].…”
Section: Discussionmentioning
confidence: 99%
“…In early studies exploring the effect of CL ablation on bovine pregnancy, maintenance P 4 was administered prior to CL ablation [5,6,7] or simultaneously with CL ablation [8,9,10,11,12]. In the previous cases, pregnancy was maintained until near the end of gestation; however, it is unknown if pregnancy can be maintained when maintenance P 4 is administered after PGF 2α administration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2005c) found no effects on subsequent pregnancy losses in cows that were pregnant at the time of treatment. In beef cows without a primary corpus luteum, the ability of corpora lutea to maintain pregnancy was greater when induced after rather than before day 36 of gestation (Bridges et al. 2000).…”
Section: Treatment With Gonadotrophins (Gnrh or Hcg)mentioning
confidence: 99%